FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING DI KABUPATEN KONAWE SELATAN: Factors That Are Related To Stunting Events In South Konawe District - Prastiwi Suhartin (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2020)
Stunting is a condition in children who have short or very short posture based on anthropometric measurements of height and age caused by chronic malnutrition, and if it survives it can reduce the child's life expectancy. Short-term nutritional problems result in an increased risk of morbidity and death, impeded development of cognitive, motor, and linguistic functions, impaired physical growth, and metabolic disorders in the body. Whereas in the long run, nutritional problems can cause a decrease in height growth in adulthood, an increased risk of obesity and accompanying diseases, a decrease in reproductive health, decreased immunity so that it can easily get sick, decrease cognitive and learning capacity, and decrease work productivity. The research objective to be achieved is to analyze factors related to the incidence of stunting in infants, with a sample of 284 respondents using proportional random sampling techniques and using matching age, sex, and place of residence. Samples are divided into two groups, namely the sample group and the control group. The dependent variable of this study is stunting, while the independent variables are hypertension, birth spacing, anemia, number of family members, exclusive breastfeeding, supplementary feeding and complementary feeding, and infectious diseases. Data were collected using a questionnaire and analyzed using Chi Square. The results showed that hypertension during pregnancy was associated with the incidence of stunting, birth spacing was associated with the incidence of stunting, anemia during pregnancy was associated with the incidence of stunting.